Application of Geochemical Indices in Evaluating Potentially Harmful Element Contamination at Mining Centres in the Sanyati Catchment, Zimbabwe - Mudimbu, Daina; Davies, Theophilus C.; Tagwireyi, Dexter; Meck, Maideyi L. (Frontiers in Environmental Science, 2022)
The release of potentially harmful elements (PHEs) into the environment in mineralised and mining areas has been associated with a variety of health-related disorders, especially non-communicable diseases such as cancer, heart and kidney failure and mental and cardiovascular disorders. The present study sought to evaluate the application of geochemical indices in assessing the degree of contamination at two sites, Kadoma and Hurungwe, both within the Sanyati Catchment, an important mining and agricultural hub in Zimbabwe. This evaluation was conducted by determining the concentration levels of 16 PHEs in 58 top-soil and stream sediment sample locations. The samples were collected during the period 2015-2017 and analysed for total PHE content using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). To assess the degree of contamination of the soils and stream sediments, contamination indices were computed and the potential ecological risk to the area was evaluated. A correlation analysis revealed PHE associations as strongly influenced by lithology and Au mineralisation in the Kadoma setting. Assessment of multi-element contamination using the pollution load index revealed significant contamination in 52% of the soil sample sites and 38% of the sediment sample sites in Kadoma. The results indicate that As, Cr, Mo and Sb are the main contaminant PHEs in the Kadoma site. Potential ecological risk ranged from moderate to very high at 71% of soil sample locations and 53% of sediment locations and the key contributors were Sb, As and Hg. At the Hurungwe site, Cr and Mo were found to be key contaminants with a low potential ecological risk for all samples. This study demonstrates the successful application of geochemical indices in evaluating the degree of single and multi-element contamination as the first step toward a human health risk assessment in mining environments. It is expected that these results would assist municipal authorities in their effort to formulate credible mitigative measures to protect the environmental health of sites and make an informed decision regarding land use planning and post-mining rehabilitation of contaminated land at mining centres.